2014
DOI: 10.1159/000368075
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Cord Ischemia Secondary to Transcatheter Arterial Chemoembolization for Hepatocellular Carcinoma

Abstract: Transcatheter arterial chemoembolization (TACE) is accepted worldwide as an effective treatment for patients with unresectable hepatocellular carcinoma. Although considered relatively safe, TACE has been associated with several complications. Spinal cord ischemia secondary to TACE is an extremely rare but disastrous complication. We report a very rare case of spinal cord injuries after TACE, together with a literature review. During the procedure, the patient suddenly experienced sensory impairment below the T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 11 publications
0
3
0
5
Order By: Relevance
“…Tu et al [ 6 ] identified liver rupture, liver abscess, femoral arterial pseudoaneurysm, cholecystitis, biloma, and pulmonary embolism as the most common severe complications of TACE. Ischemic complications, encompassing spinal cord ischemia [ 16 ], esophageal ischemia [ 8 ], ischemic cholecystitis, and bile duct necrosis [ 17 ], as well as ischemia near the gastroduodenal arterial supply [ 7 , 8 ], are rare but can be severe and accompanied by a high mortality rate. The dominating symptoms in all cases were abdominal pain and fever that mostly occurred within 2 weeks after intervention [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tu et al [ 6 ] identified liver rupture, liver abscess, femoral arterial pseudoaneurysm, cholecystitis, biloma, and pulmonary embolism as the most common severe complications of TACE. Ischemic complications, encompassing spinal cord ischemia [ 16 ], esophageal ischemia [ 8 ], ischemic cholecystitis, and bile duct necrosis [ 17 ], as well as ischemia near the gastroduodenal arterial supply [ 7 , 8 ], are rare but can be severe and accompanied by a high mortality rate. The dominating symptoms in all cases were abdominal pain and fever that mostly occurred within 2 weeks after intervention [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the risk of complications such as partial necrosis [ 18 ], pseudocyst or abscess formation [ 21 ], and potentially fatal sepsis, especially when diagnosed at a late stage, underscores the importance of early diagnosis and differentiation from postembolic syndrome. Consequently, most authors recommend measuring lipase and/or amylase in all patients with postinterventional abdominal pain [ 16 , 18 , 19 ]. However, normal serum amylase and lipase levels in our patient with severe necrotizing pancreatitis indicate the need for radiological tools to exclude ischemic pancreatitis after TACE.…”
Section: Discussionmentioning
confidence: 99%
“…La quimioembolización transarterial, o TACE, es un procedimiento no quirúrgico y mínimamente invasivo que consiste en combinar la administración local de quimioterapia con un procedimiento llamado embolización. Este procedimiento se puede utilizar para tratar el cáncer de mama, especialmente el de tipo metastásico (5) . Aunque se considera relativamente seguro, se ha asociado con varias complicaciones, incluida la isquemia de la médula espinal (5) .…”
Section: Introductionunclassified
“…Este procedimiento se puede utilizar para tratar el cáncer de mama, especialmente el de tipo metastásico (5) . Aunque se considera relativamente seguro, se ha asociado con varias complicaciones, incluida la isquemia de la médula espinal (5) .…”
Section: Introductionunclassified
See 1 more Smart Citation